Implementation of HPV-based screening in Burkina Faso: lessons learned from the PARACAO hybrid-effectiveness study - Keitly Mensah; Charles Kaboré; Salifou Zeba; Magali Bouchon; Véronique Duchesne; Dolorès Pourette; Pierre DeBeaudrap; Alexandre Dumont (BMC, 2021)
Abstract Background Cervical cancer screening in sub-Saharan countries relies on primary visual inspection with acetic acid (VIA). Primary human papillomavirus (HPV)-based screening is considered a promising alternative. However, the implementation and real-life effectiveness of this strategy at the primary-care level in limited-resource contexts remain under explored. In Ouagadougou, Burkina Faso, free HPV-based screening was implemented in 2019 in two primary healthcare centers. We carried out a process and effectiveness evaluation of this intervention. Methods Effectiveness outcomes and implementation indicators were assessed through a cohort study of screened women, observations in participating centers, individual interviews with women and healthcare providers and monitoring reports. Effectiveness outcomes were screening completeness and women's satisfaction. Logistic regression models and concurrent qualitative analysis explored how implementation variability, acceptability by women and the context affected effectiveness outcomes. Results After a 3-month implementation period, of the 350 women included in the cohort, 94% completed the screening, although only 26% had their screening completed in a single visit as planned in the protocol. The proportion of highly satisfied women was higher after result disclosure (95%) than after sampling (65%). A good understanding of the screening results and recommendations increased screening completeness and women's satisfaction, while time to result disclosure decreased satisfaction. Adaptations were made to fit healthcare workers' workload. Conclusion Free HPV-based screening was successfully integrated within primary care in Ouagadougou, Burkina Faso, leading to a high level of screening completeness despite the frequent use of multiple visits. Future implementation in primary healthcare centers needs to improve counseling and reduce wait times at the various steps of the screening sequence.